2018
DOI: 10.1002/app.46411
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray‐assisted fabrication of core‐shell arabinoxylan gel particles for insulin and probiotics entrapment

Abstract: This work presents the fabrication and characterization of electro-sprayed core-shell particles that were composed of maize bran arabinoxylans (MBAX) with insulin in the core, and maize wastewater arabinoxylans (MWAX) with Bifidobacterium in the shell. Two concentrations of MBAX (3% and 6% w/v) and MWAX (6% and 10% w/v) were evaluated. The particles fabricated with MBAX at 6% (w/v) in the core and MWAX at 10% (w/v) in the shell were more stable, presented spherical shape and no aggregation being therefore sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 47 publications
(88 reference statements)
1
23
1
Order By: Relevance
“…A microspheres yield of 53.5 ± 3.8% and an insulin loading of 34.5 ± 1.3% were obtained for AX microspheres at 2% (w/v). The value obtained for encapsulation efficiency was 71.3 ± 2.7%, which is similar to those reported in alginate microspheres (65–79%w/w) and AX‐insulin beads (72%) …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…A microspheres yield of 53.5 ± 3.8% and an insulin loading of 34.5 ± 1.3% were obtained for AX microspheres at 2% (w/v). The value obtained for encapsulation efficiency was 71.3 ± 2.7%, which is similar to those reported in alginate microspheres (65–79%w/w) and AX‐insulin beads (72%) …”
Section: Resultssupporting
confidence: 85%
“…The microspheres size distribution is presented in Figure (b), the primary size population was found between 150 and 300 μm and the mean particle diameter was 233 μm. This average diameter size is smaller than that reported for other AX spheres (531 μm to 2.9 mm) …”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…These gels have the ability to entrap and control the release of model biomolecules such as lycopene, lactoglobulin, and insulin . In addition, they can be used for the encapsulation of yeast and probiotic bacteria (Bifidobacteria) . Recently, the entrapment of probiotic bacteria (Bifidobacteria) and insulin in core–shell AX gel particles were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the entrapment of probiotic bacteria (Bifidobacteria) and insulin in core–shell AX gel particles were evaluated. The simulation of gastrointestinal conditions demonstrated that 76% of the insulin carried is released in the colon, indicating that these gels could be used as an alternative system for the delivery of insulin and probiotics targeted to colon for the treatment of diabetes . Considering that AX gels can be degraded by the colonic microbiota and exhibit antioxidant activity, they could be considered as an excellent alternative for the development of colon‐targeted drug delivery systems for the treatment of diseases such as diabetes and colon cancer …”
Section: Introductionmentioning
confidence: 99%